-6x+5(-2x-6)=-40-6x

Simple and best practice solution for -6x+5(-2x-6)=-40-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+5(-2x-6)=-40-6x equation:


Simplifying
-6x + 5(-2x + -6) = -40 + -6x

Reorder the terms:
-6x + 5(-6 + -2x) = -40 + -6x
-6x + (-6 * 5 + -2x * 5) = -40 + -6x
-6x + (-30 + -10x) = -40 + -6x

Reorder the terms:
-30 + -6x + -10x = -40 + -6x

Combine like terms: -6x + -10x = -16x
-30 + -16x = -40 + -6x

Solving
-30 + -16x = -40 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-30 + -16x + 6x = -40 + -6x + 6x

Combine like terms: -16x + 6x = -10x
-30 + -10x = -40 + -6x + 6x

Combine like terms: -6x + 6x = 0
-30 + -10x = -40 + 0
-30 + -10x = -40

Add '30' to each side of the equation.
-30 + 30 + -10x = -40 + 30

Combine like terms: -30 + 30 = 0
0 + -10x = -40 + 30
-10x = -40 + 30

Combine like terms: -40 + 30 = -10
-10x = -10

Divide each side by '-10'.
x = 1

Simplifying
x = 1

See similar equations:

| x-y=.2 | | x-y=.19 | | 3xy+4x+y=15 | | 3(3x-2)+21=7x+3 | | 9x+2-10x= | | 39=w | | 3(3x-2)+21=7x | | -3k=7(k-20) | | -39=w | | 11=4(x-1) | | x^2-100x+3025=0 | | r/(-51)=-156 | | -w=39 | | 5x+27=4x+28 | | -22p-6(6-5p)=4(p-3)-36 | | 2ax+5=6x+1 | | X^29x+14=0 | | 3v-6=-12 | | -5w=22 | | 15+3x=39+x | | 5ax+5=6x+1 | | 15x-9=8x+21 | | -9x+3x=18 | | (4x+6)+90=136 | | 21-(x+6)=8x-3 | | 5x-4x+3x-16=8 | | 136+90+(4x+6)=360 | | -(6y+w)-2(-2w+4y)= | | w=39 | | 0.35/3=18/c | | 4x+10=6x+15 | | x-2(x+3)=0 |

Equations solver categories